Women’s participation in decision making process (shuraa) : views of Muslim jurists. - Md. Sarkam, Mohd Kamarul Amree; Awang Hamat, Mohd Afandi (Kulliyyah of IRKHS, International Islamic University Malaysia, 2012)
This article will expose the Muslim Jurists’ opinions with regards to the women’s participation in politics generally and in shura council (decision making process) particularly. In fact, Muslim Jurists have different opinions whether women are allowed to participate in shura council or vice versa. Since this article is basically based on the Islamic legal jurisprudence (fiqh), the article then will highlight views of Muslim jurists as well as their evidences which derived from various Sharie sources. This article will also provide the root cause of differences (tahrir mahal an-niza‘) among Muslim Jurists on the issue of women’s participation in decision making process (Sharie). At the end, this article will highlight which of their views are considered as a strong views (rajih) on this regard.